2022
DOI: 10.1371/journal.pone.0264653
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of venous thromboembolism after the initiation of chemotherapy predicts a poor prognosis in patients with unresectable metastatic pancreatic cancer who underwent first-line chemotherapy with gemcitabine plus nab-paclitaxel

Abstract: Background Pancreatic cancer is associated with a high thromboembolism risk. We investigated the significance of early venous thromboembolism (VTE) detection in patients with unresectable metastatic pancreatic cancer (UR-MPC) who received first-line chemotherapy with gemcitabine plus nab-paclitaxel (GnP). Methods This single-center retrospective study enrolled 174 patients with UR-MPC who underwent GnP as a first-line chemotherapy from April 2017 to March 2020. The early detection of VTE (deep venous thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The sample sizes in these studies ranged from 170 to 838. Among the ten studies, 1,903 Asian patients ( 17 , 18 , 20 , 22 , 23 ) and 1,242 European and American patients ( 14 16 , 19 , 21 ) were enrolled. The majority of the patients were middle-aged and elderly individuals diagnosed with advanced pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes in these studies ranged from 170 to 838. Among the ten studies, 1,903 Asian patients ( 17 , 18 , 20 , 22 , 23 ) and 1,242 European and American patients ( 14 16 , 19 , 21 ) were enrolled. The majority of the patients were middle-aged and elderly individuals diagnosed with advanced pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the patients were middle-aged and elderly individuals diagnosed with advanced pancreatic cancer. Treatment modalities included chemotherapy ( 14 16 , 18 20 , 22 , 23 ) or chemoradiotherapy ( 17 , 21 ). Our research aimed to assess the predictive value of VTE in patients with advanced pancreatic cancer by combining OS and DFS data.…”
Section: Resultsmentioning
confidence: 99%
“…26 particularly in early VTE, which was defined as within 1.5 months after the initiation of chemotherapy or within 3 months after diagnosis of PDAC. 7,9,13,16 Other studies reported that the occurrence of VTE does not significantly affect the prognosis. 5,8,11,14 As mentioned above, this is probably explained by the difference in the study population among studies.…”
Section: Risk Factors Associated With Overall Survivalmentioning
confidence: 99%
“…7,9,10, 12,16 . On the contrary, several studies reported that the occurrence of VTE was not associated with OS.…”
Section: Introductionmentioning
confidence: 99%
“…[104][105][106] In patients with PDAC, iron deficiency rates of 60% and anemia rates of 30% at diagnosis have been reported. [105][106][107][108] Chemotherapy can cause or worsen anemia. PDAC patients are regularly treated with chemotherapy regimens containing one or more of the following chemotherapeutic agents; 5-fluorouracil, gemcitabine, irinotecan, nab-paclitaxel, and oxaliplatin, for which anemia incidences around 80 to 90% have been found.…”
Section: Red Blood Cellsmentioning
confidence: 99%